A neglected case of Sacrococcygeal teratoma in a neonate - Mondal, Monojit; Biswas, Biswajit; Roy, Atanu; Ari, Abhijit; Nayek, Kaustav; Datta, Asok Kumar; Rana, Kriti Sundar; Banerji, Nayan (Asian Journal of Medical Sciences, 2014)
Sacrococcygeal teratoma (SCT), although rare, is the most common congenital neoplasm in neonates. A mass in the sacrococcygeal region at the time of birth is the usual presentation. Routine antenatal abdominal ultrasound of mother can detect almost all the cases. The prognosis is favorable when diagnosis is done antenatally and proper management is instituted soon after the baby is born. Presented herein a 2 days old neonate with a neglected SCT who died unfortunately due to massive bleeding from the tumor. A brief review of the literature has been presented to make everyone aware of the condition so that future recurrence of such sad events may be avoided. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10448 Asian Journal of Medical Sciences Vol.6(2) 2015 108-110